Key technology and validation of roadside sensing system for vehicle-road cooperation - BAO Xuyan; GONG Zheng; LI Boxiong; YU Bingyan (Dianxin kexue)
Vehicular-road collaborative roadside sensing systems are a crucial part of developing “integrated vehicular-road-cloud systems” and implementing the digital transformation and upgrading of transportation infrastructure. Based on current application needs and industrial progress, key technologies and the standardization status of the system were analyzed, and the testing tools and verification results developed by the research team were presented.The results of testing and verification show that some deployed roadside sensing systems still have a significant technological gap to be fulfilled, and with the aid of testing tools, system performance can be greatly improved. The necessity of key technologies, the usability of existing standards, and the high value of testing tools have all been confirmed.